Pengaruh Karakteristik Perusahaan Terhadap Pengungkapan Kesehatan dan Keselamatan Kerja: Studi Empiris pada Perusahaan Infrastruktur dan Pertambangan yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2019-2021 - Susanty, Angella Natalia; Aminah (Jurnal EMT KITA, 2024)
Disclosure of occupational health and safety is a crucial aspect of corporate social responsibility, requiring in-depth attention from the company. This research aims to analyze the impact of company size, leverage, and company age on Occupational Health and Safety (K3) disclosure. The research object involves infrastructure and mining companies listed on the Indonesia Stock Exchange during the 2019-2021 period. The method applied is panel data regression analysis. The research results show that company size and company age have a positive effect on occupational health and safety disclosures, while leverage has a negative effect on occupational health and safety disclosures.